Role of Cu‐doping in CdTe thin films: Experiments and simulations. (21st November 2022) - Singh, Ranveer; Vallet, Maxime; Singh, Vijay; Srivastava, Sanjeev K.; Claverie, Alain; Som, Tapobrata
Abstract : Due to its outstanding physical properties, CdTe is used to fabricate high efficiency solar cells. However, its high work function poses a challenge, and hence, to fabricate an efficient CdTe‐based solar cell, Cu‐doping may be useful. Here, we present the role of temperature‐dependent Cu‐doping in radio frequency sputter‐deposited CdTe films and the related changes occurring in their optical, electrical, structural and microstructural properties. For instance, Cu‐doping at different temperatures leads to an increase in the grain size and a reduction in the optical reflectance with increasing temperature. In addition, Kelvin probe force microscopy measurements reveal that the work function is found to be smaller corresponding to the annealing temperature of 473 K, whereas resistivity measurements show that it decreases with increasing temperature (the lowest value of resistivity is found to be 1.8 × 10 −2  Ω‐cm). To understand the electronic structure of CdTe before and after Cu‐doping, we have carried out first‐principles density functional theory (DFT) simulation, which reveals a strong hybridization among Cu, Cd and Te atoms. This study paves the way to fabricate efficient Cu‐doped CdTe‐based solar cells.